THE THE COMPARISON OF INTERVENTION BETWEEN AUTO STRETCHING AND ACTIVE ISOLATED STRETCHING ON REDUCTION OF UPPER TRAPEZIUS MUSCLE PAIN ON CIVIL SERVANTS OF MINISTRY OF MARTIME AND FISHERIES IN BALI PROVINCE - Putra, I Gusti Bagus Ari Pradnyana; Wibawa, Ari; Purnawati, Susy; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p12, 2018)
ABSTRACT The research is aimed to know abour the difference between Auto Stretching exercise and Active Isolated Stretching on reduction of Upper Trapezius muscle pain on civil Servants of Ministry of Maritime and Fisheries in Bali Province. The giving of intervention of Active Isolated Stretching was better in reducing Upper Trapezius muscle pain than Auto Stretching intervention of office employees. This research was experimental randomized pre-post test two group design which involved 24 people as samples which was divided into 2 groups, the firs group with Auto Stretching and the second with Active Isolated Stretching. After getting the results, the normality test was done using Levene’s test for further, statistic test was done using Independent Sample T-test. The results of the test shown that the mean of the first group (1,16±0,167) and the second group (1,66±0,220) and would mean (p < 0,05). The conclusion of this research is Active Isolated Stretching reduced more Upper Trapezius muscle pain intensity than Auto Stretching on Civil Servants of Ministry of Maritime and Fisheries in Bali Province. Keywords: Auto Stretching, Active Isolated stretching, Upper Trapezius Muscle, VAS.